2020
DOI: 10.3390/atmos11050510
|View full text |Cite
|
Sign up to set email alerts
|

Air Quality in Brno City Parks

Abstract: Parks embody an important element of urban infrastructure and a basic type of public space that shapes the overall character of a city. They form a counterweight to built-up areas and public spaces with paved surfaces. In this context, parks compensate for the lack of natural, open landscapes in cities and thus have a fundamental impact on the quality of life of their inhabitants. For this reason, it is important to consider the quality of the environment in urban parks, air quality in particular. Concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In spite of a general belief that green urban areas provide the best air quality within the city, the measurements supporting this claim are mostly lacking. Based on four 14-day campaigns measuring NO, NO 2 , PM 10 , and O 3 levels, Huzlík et al [18] concluded that the air quality in the parks approached that of the urban background sites, except for Koliště park, where similar ambient air pollution levels as at the traffic site were measured.…”
Section: Regional and Urban Background Ambient Air Pollutionmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of a general belief that green urban areas provide the best air quality within the city, the measurements supporting this claim are mostly lacking. Based on four 14-day campaigns measuring NO, NO 2 , PM 10 , and O 3 levels, Huzlík et al [18] concluded that the air quality in the parks approached that of the urban background sites, except for Koliště park, where similar ambient air pollution levels as at the traffic site were measured.…”
Section: Regional and Urban Background Ambient Air Pollutionmentioning
confidence: 99%
“…Huzlík et al [18] examined the ambient air quality in park areas in Brno, the second largest city of the CR. In spite of a general belief that green urban areas provide the best air quality within the city, the measurements supporting this claim are mostly lacking.…”
Section: Regional and Urban Background Ambient Air Pollutionmentioning
confidence: 99%
“…All the PTEs reached increased values in the southeast part of the botanical garden near a busy crossroad. Such places are highly contaminated with PTEs and other pollutants due to stop-and-go traffic [17,19,46,47]. Road and tram traffic are a likely source of this enrichment with PTEs as one of the main emitters of urban contamination [5,19,48,49].…”
Section: Soil Contamination Assessmentmentioning
confidence: 99%
“…They improve city dwellers' living conditions through functions such as climate regulation, sustaining biogeochemical cycles, water flow regulation, runoff mitigation and pollutant retention [6,11,[13][14][15]. UGS are often considered less polluted [16,17] and sometimes even used to determine background values for environmental contamination assessment [18,19]. However, due to their potential to retain and store pollutants, they may become hotspots of accumulated pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Urban open green spaces are generally regarded as being the places that provide the best air quality in a city and as spots where urban dwellers can relax, in addition to supporting the conservation of biodiversity (Lee et al, 2014;Huzlík et al, 2020). Open green lands create an urban setting for public interaction and a venue for recreation, education, and exploration.…”
Section: Introductionmentioning
confidence: 99%